Pengaruh Perbandingan Nilai Total Suspended Solid Jambu Biji Kristal (Psidium guajava L.) dengan Jambu Biji Merah (P. pomiferum L.) Terhadap Peningkatan Produksi di Desa Neglasari - Sang Ayu Made Sri Tandewi; Yannefri Bakhtiar; Amiruddin Saleh (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Mekarsari village as a village located in Neglasari Village which has various potential natural resources in the agricultural sector that was developed. At present the horticultural commodity intensification activity in the form of fruit plants in Neglasari Village has been carried out, namely guava planting. The purpose of this activity is to study the differences in the level of sweetness in the growth of guava crystals and red guava as well as the sweetness level factors in guava in Kampung Mekarsari, Neglasari Village, Dramaga District, Bogor Regency, West Java Province through the Six Universities Initiative Japan- Indonesia Service and Learning Program (SUIJI-SLP) 2020. The type of data used in this activity is primary data obtained through direct interviews with guava farmers, village officials, and the people of Kampars Mekarsari, Neglasari Village and secondary data obtained from those from from several agencies. Testing the sweetness of the fruit is done using a refractometer. Based on the results of tests that have been done, the TSS (Total Suspended Solid) test on red guava was 7.22% brik, while the TSS (Total Suspended Solid) test on crystal guava was 8.35% brik. The difference in the level of sweetness is caused by several factors, such as the use of KCL fertilizer which can increase the level of sweetness and vitamin C content in fruit maturation and fruit control from pests by wrapping using white HDPE plastic on crystal guava affects the quality of the guava. Keywords: Crystal guava, red guava, Mekarsari village farmers, Total Suspended Solid level.